Parenting Bagi Anggota Persit Kartika Chandra Kirana dalam Mendukung Program Pendidikan Keluarga - Revita Yanuarsari; Fanny Fanny Rizkiyani (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2016)
Children are a budding nation that will continue the ideals of the Indonesian nation, so the education of children in the family is important, in order to create quality for future generations. Parenting in the home can affect the development and growth of children, so the family to be the beginning of character education for children. Housing Complex Environmental Transport Department of Military Region (Hubdam) III Regional Military Command (KODAM) Siliwangi potentially give birth to children of noble character and intelligent. But so far there are still many children who fail to thrive well, especially in the social aspects of emotional. This is the impact of the lack of family-based education. Therefore parenting program aims to improve the quality of family communication at home, is also able to provide knowledge for all members of the Union of Soldiers Wife Kartika Chandra Kirana (PERSIT) in HUBDAM III / Siliwangi to further improve the education of the best character of the house.